Universal Curie constant and pyroelectricity in doped ferroelectric HfO2 thin films. (August 2020) - Lomenzo, Patrick D.; Jachalke, Sven; Stoecker, Hartmut; Mehner, Erik; Richter, Claudia; Mikolajick, Thomas; Schroeder, Uwe
Abstract: Pyroelectric coefficients are measured for Si, Sr, La, Al, and Gd doped HfO2 thin films as well as the solid-solution Hf0.5 Zr0.5 O2 composition from 280 to 440 K. Pyroelectric currents show sensitivity to the dopant used to stabilize ferroelectricity in HfO2 . Large pyroelectric coefficients up to 70 μC cm −2  K −1 were measured in films with the largest remanent polarization magnitudes, La-doped HfO2 and Hf0.5 Zr0.5 O2 . A temperature-driven ferroelectric to antiferroelectric-like transition influences the pyroelectric coefficient and is found only in Si-doped HfO2 thin films. The transition is shown to produce a decrease in the Curie constant with temperature and thus deviates from the Curie law, although most ferroelectric films reported here obey the Curie law. Independent measurements of the remanent polarization, relative permittivity, and pyroelectric coefficient are used to extract the Curie constants of the thin films. The fundamental thermodynamic relationship between the dielectric, ferroelectric, and pyroelectric properties of ferroelectric HfO2 thin films are established based on Landau theory with a universal Curie constant of 5.8 × 10 −7 ± 0.46 × 10 −7  K C V −1 m −1 (Landau coefficient, α0  = 1.72 × 10 6  ± 0.138 × 10 6  V m K −1 C −1 ) for ferroelectric HfO2 independent of doping concentration and dopant type. An electro-thermal coupling factor of 1.9 × 10 −3 and a voltage responsivity figure of merit of 0.085 m 2 /C illustrate the promising potential of ferroelectric HfO2 thin films for use in embedded energy harvesting and infrared sensing circuits. Graphical abstract: Image 1 Highlights: Pyroelectric coefficients of up to −70 μC/m 2 were measured in HZO, Si, La, Gd, Sr, and Al-doped HfO2 . Pyroelectricity in FE HfO2 is proven to be compatible with the Landau free energy model. A universal Curie constant of 5.8 × 10 −7  K C V −1 m −1 is obtained independent of doping. Deviations in the Curie law were observed near phase transitions in Si-doped HfO2 .